Protocolo Para Gerenciamento Hierárquico de Redes de Computadores e deTelecomunicações 10.14209/jcis.2001.11 - Porto Fernandez, Marcial; Moreira Delfino, Gardel; de Castro P. Pedroza, Aloysio (Journal of Communication and Information Systems, 2015)
A computer network management system usually presents a management process (manager-agent). The management of large networks demands more computer resources and management system capacity, impossible to achieve with just one manager. The TMN (Telecommunications Management Network) standard, that intends to standardize management systems for telecommunication networks offering those resources, foresees the use of several managers organized in a hierarchical architecture. This work presents a study of the problems in managing large networks and proposes a protocol for a Hierarchical Management System (SGH). Although we use an example of telecommunication network, the SGH system is suitable for Internet. The SGH protocol is specified using the formal description language Estelle and its functionality is verified using a test model.